Korrekturen und Ergänzungen zum ’Lepidopterorum Catalogus, Fasc. 118, Noctuidae’ von R. Poole (Insecta, Lepidoptera, Noctuidae). Teil 1. - Steiner, Axel (Contributions to Entomology = Beiträge zur Entomologie, 1994)
This is the first paper of a series containing addenda and corrigenda to the Noctuidae part of the Lepidopterorum Catalogus. The following errors are treated: taxa belonging to other families listed in the catalogue as unidentified Noctuid taxa; Noctuid taxa omitted in the catalogue; subspecific taxa erroneously treated as infrasubspecific, and vice versa; incorrect type localities; incorrect dates of publication; some important typographical errors. New taxa and nomenclatural changes published since 1980 are not included. Note: English translations of this article can be obtained from the author against international reply coupon.